Commerce and the Celtic Revival : the history of the Irish facsimile industry, 1840-1940 - Kelly, Tara A. (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2013)
Broadly speaking, this thesis has demonstrated that as a category facsimiles of Irish archaeological jewellery and metalwork are not merely derivative works, but have aesthetic and cultural value worthy of a devoted study. The first chapter focused on the key commercial firms, institutions, artefacts and manufacturing processes associated with the production of facsimiles in Dublin.
Keywords: History of Art, Ph.D.; Ph.D. Trinity College Dublin